Employee Retention Strategy Based on Employee Engagement in Retaining High Performing Employees - Rio Mattajang (Dalihan Na Tolu: Jurnal Hukum, Politik dan Komunikasi Indonesia, 2023)
Employee engagement has been widely recognized as a key factor in retaining competent and high-performing employees in organizations. This research aims to explore and analyze employee retention strategies that focus on employee engagement in the work environment. This research uses a qualitative approach with descriptive methods. The research results show that implementing strategies to increase employee retention based on employee engagement has a positive impact on employee loyalty to the company. It was found that solid orientation, positive company culture, listening to employee feedback, providing rewards, providing promotion opportunities, paying attention to work-life balance, and providing correct information about the company are important factors that contribute to employee engagement. By implementing these strategies, organizations can achieve higher employee retention, increase job satisfaction, and create a productive and sustainable work environment.